Expressing and Examining Morality in Everyday Life: Social Comparisons among Swedish Parents of Deaf Children - Åkerström, Malin; Jacobsson, Katarina (Qualitative Sociology Review, 2009)
Social comparisons, seeing oneself in relation to others, are universal, common, and perhaps even necessary. In a study of parents of deaf children, intense, open, and mutual examinations were voiced in parental groups, meetings between parents and professionals, and interviews. These comparisons were generated in a specific situation created by successful claims for separate milieus advocated by the Deaf movement. The local culture, “the deaf world,” was characterized by close proximity and a highly charged ideological moral climate. With the central argument that strong integration breeds comparisons and examinations, we conclude that the integration of parents creates a situation perfect for drawing comparisons, creating not only cohesion, but also renewed separatist distinctions, expressed in terms of moral examinations, competition and envy. Studying the content and details of comparisons in any given field makes the particular morality that is bred, fed, and elaborated obvious.